Effect of Auditable Pharmaceutical Services and Transaction System on Pharmaceutical Service Outcomes in Public Hospitals of SNNPR, Ethiopia - Beyene D; Abuye H; Tilahun G (Dove Medical Press, 2020)
Deginet Beyene,1 Habtamu Abuye,2 Gizachew Tilahun3 1Pharmaceutical Supply Chain Management, Pharmacy Department Unit, Doctor Bogalech Gebre Memorial General Hospital, Durame, Ethiopia; 2Department of Pharmacy, College of Medicine and Health Sciences, Wachemo University, Hossana, Ethiopia; 3Pharmacoepidemiology and Social Pharmacy Department, School of Pharmacy, Institute of Health Sciences, Jimma University, Jimma, EthiopiaCorrespondence: Habtamu AbuyeWachemo University, P.O. Box: 667, Tel +521 913571974Fax +251-46-555-19-30Email harohabe@gmail.comBackground: Auditable pharmaceuticals service and transaction system (APTS) is unique in its systems strengthening approach. It is a data-driven package of interventions designed to establish accountable, transparent, and responsible pharmacy practice. The objective of this study was to assess the outcome performance of pharmaceuticals services among selected hospitals with and without the APTS system in SNNPR, Ethiopia.Methods: A cross-sectional comparative facility-based study was conducted at public hospitals by using an intervention and control approach to estimate the significance of the difference between average performances of APTS and non-APTS hospitals. A case-to-control ratio was applied to decide the number of sites and a simple random lottery sampling technique was employed to select control sites. The sample size formula was used to determine the proposed population for patient care indicator assessment. Epidata version 3.1 and SPSS version 23 were used for analysis. The study was conducted from March 1 to 30, 2019.Results: APTS implemented hospitals attained 92.3% patient satisfaction on the overall pharmacy services compared to 47.5% for non-APTS hospitals. They have improved essential drugs (EDs) availability, minimum stock-outs, and reduced wastage rates, unlike control groups. They undertook workload analysis to assess human power sufficiency; generate reliable information from accurate recording culture for decision making; practiced transparency and accountability through conducting physical inventory and daily sales tracking/management system; and made budget utilization rationale applying ABC analysis, VEN analysis, ABC/VEN reconciliation, and stock status analysis (SSA) that non-APTS hospitals did less/not.Conclusion: In general, higher performances were observed in APTS implemented hospitals than non-APTS hospitals regarding patient knowledge, satisfaction, and medicine availability at stores. In all cases, it needs improvement to achieve target values.Keywords: APTS, transparency, accountability, satisfaction, availability, stock out duration, wastage rate